Emissões de gases de efeito estufa e seu impacto no mercado de trabalho brasileiro: uma análise de insumo-produto - Paula, Natália Moura de (Universidade Federal de São Carlos, 2023)
The changes in the physical-chemical composition of the Earth's atmosphere due to the increase in pollutant emissions are a cause for concern for the viability of human presence on the planet. Originating mostly from anthropogenic sources, greenhouse gases (GHG) have caused a rise in global temperatures and resulted in significant climate changes. Despite the importance of the subject, there are few specific studies in Brazil to analyze the interrelationship between the labor market and the environment. Therefore, this study aims to analyze the relationship between pollutant emissions and economic performance. However, for a more specific study of the subject, in the analysis of economic performance, the research will focus on the study of employment levels. The methodology used consisted of the Leontief Model, based on the input-output matrices estimated for Brazil in 2018, and data from the Sistema de Estimativa de Emissões e Remoções de Gases de Efeito Estufa (SEEG). The results obtained allowed to identify that, without technological changes, the reduction of carbon emissions via the contraction of the most polluting sectors’ activity per existing job vacancy would cause more significant indirect effects than direct ones, since these most polluting sectors have high employment multipliers, mainly the Energy sector.
Greenhouse gases emisssions and the brazilian labor market: input-output analysis
Keywords: Gases de Efeito Estufa; Emissões; Insumo-produto; Mercado de trabalho; Emissions; Greenhouse Gases; Input-Output; Labor Market; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::METODOS QUANTITATIVOS EM ECONOMIA; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::TEORIA ECONOMICA